(untitled) (Discourse of Law and Administration, 2023)
With the expiry of 31 December 2020, Brexit has become a reality. However, already since the notification by the UK government that it intends to leave the European Union, there has been speculation as to what direction Brexit will go, i.e., whether it will be so called “no deal” Brexit, or whether the EU and the UK manage to conclude a Withdrawal Agreement. The next crucial question was how the cooperation between the EU and UK in civil and private international law, would look like. The object of this article is to present a small part of this cooperation, namely in the field of determining the law applicable to non-contractual obligations. Accordingly, the article firstly presents alternative options for the arrangement of this cooperation and then deals with its successive stages. In the last part of the article the current regulations in this area are presented, i.e., the main rule and the rules on the parties’ choice of applicable law, regulated in the Rome II Regulation on the law applicable to non-contractual obligations.